Production Management Model Based on Lean Manufacturing Focused on the Human Factor to Improve Productivity of Small Businesses in the Metalworking Sector - Huamán, Jonathan (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.